Variation in end-of-life care and hospital palliative care among hospitals and local authorities: A preliminary contribution of big data. (October 2021) - Gusmano, Michael K.; Rodwin, Victor G.; Weisz, Daniel; Cottenet, Jonathan; Quantin, Catherine
Background: Many studies explore the clinical and ethical dimensions of care at the end-of-life, but fewer use administrative data to examine individual and geographic differences, including the use of palliative care. Aim: Provide a population-based perspective on end-of-life and hospital palliative care among local authorities and hospitals in France. Design: Retrospective cohort study of care received by 17, 928 decedents 65 and over (last 6 months of life), using the French national health insurance database Results: 55.7% of decedents died in acute-care hospitals; 79% were hospitalized in them at least once; 11.7% were admitted at least once for hospital palliative care. Among 31 academic medical centers, intensive care unit admissions ranged from 12% to 67.4%; hospital palliative care admissions, from 2% to 30.6%. Across local authorities, for intensive care unit days and hospital palliative care admissions, the ratios between the values at the third and the first quartile were 2.4 and 1.5. The odds of admission for hospital palliative care or to an intensive care unit for more than 7 days were more than twice as high among people ⩽85 years (aOR = 2.11 (1.84–2.43) and aOR = 2.59 (2.12–3.17), respectively). The odds of admission for hospital palliative care were about 25% lower ( p = 0.04) among decedents living in local authorities with the lowest levels of education than those with the highest levels. Conclusion: The variation we document in end-of-life and hospital palliative care across different categories of hospitals and 95 local authorities raises important questions as to what constitutes appropriate hospital use and intensity at the end-of-life.